Effectiveness of AI Real-Time Feedback Assistance in Improving Writing Skills - Khasanah, Shokhikhatul (Belantika Pendidikan, 2025)
This study aims to examine the effectiveness of using Real- Time Feedback Assistance in improving writing skills among students. The research employs an experimental design with a pretest-posttest on two groups. The measurement tools used is a writing skills assessment rubric. Data analysis results show a significant difference between the writing skills scores of students in the experimental group (M= 82, SE=4.68 ) and the control group (M= 74 , SE= 6.94 ) after the intervention. These findings indicate that the use of real- time AI feedback assistance has a positive impact on improving students ' writing skills, making it an effective approach to enhance writing skills.